(untitled) - Pescod, M. B. (Rome, 1992)
The book is presented as a guide to the use to the use of treatment effluent for irrigation and aquaculture. It presents the lastest views on health risks, enviromental hazards and crop production potential asssociated with the use of treatment wastewater. It is also intended to provide guidance to national planners and decision-makers, agricultural and municipal managers, field engineers and scientists, health and agricultural field workers, wastewater treatment plant operator and farmers.
Keywords: Sewage irrigation,Irrigation farming